2020
DOI: 10.1111/jgh.15309
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term outcomes of endoscopic submucosal dissection and transanal endoscopic microsurgery for the treatment of rectal tumors

Abstract: Background and Aim Endoscopic submucosal dissection and transanal endoscopic microsurgery are good options for the treatment of rectal adenomas and early rectal carcinomas, but whether long‐term outcomes of these procedures are comparable is not known. The aim of this study was to address this question. Methods A retrospective single‐center study evaluating 98 consecutive procedures between June 2008 and December 2017 was performed in a tertiary cancer center. Consecutive patients who had undergone either endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…[19][20][21][22][23][24] For large ultra-low rectal GISTs, traditional radical resection may cause severe sphincter injury, urinary Compared with TEM, ESD has similar en bloc and R0 resection rates, shorter hospital stay, and lower rates of late complications and recurrence for resection of early rectal adenocarcinoma and adenoma. 25 However, there have been no studies comparing the efficacy between ESD and other minimally invasive surgeries for the treatment of rectal GISTs as yet. Kim et al reported a case in which a 5.5 cm  4.0 cm rectal GIST was treated effectively by ESD without preoperative imatinib.…”
Section: Suchmentioning
confidence: 99%
“…[19][20][21][22][23][24] For large ultra-low rectal GISTs, traditional radical resection may cause severe sphincter injury, urinary Compared with TEM, ESD has similar en bloc and R0 resection rates, shorter hospital stay, and lower rates of late complications and recurrence for resection of early rectal adenocarcinoma and adenoma. 25 However, there have been no studies comparing the efficacy between ESD and other minimally invasive surgeries for the treatment of rectal GISTs as yet. Kim et al reported a case in which a 5.5 cm  4.0 cm rectal GIST was treated effectively by ESD without preoperative imatinib.…”
Section: Suchmentioning
confidence: 99%
“…[10][11][12][13] It allows a high rate of en bloc resection and a lower recurrence rate than EMR, [14][15][16][17][18] or even transanal endoscopic microsurgery (TEM). 19 Several studies have described the successful outcomes of colorectal ESD and the high accuracy of magnification chromoendoscopy. However, the impact of routinely implementing those procedures on the number of abdominal surgeries for nonmalignant colorectal polyps has not been described.…”
Section: E836mentioning
confidence: 99%
“…10–13 It allows a high rate of en bloc resection and a lower recurrence rate than EMR, 14–18 or even transanal endoscopic microsurgery (TEM). 19…”
mentioning
confidence: 99%
“…However, the TEM technique also has higher anaesthesia-related adverse events and postoperative morbidity ( 11 ). Most critically, TEM is not more effective over the long run than ESD ( 14 ). Currently, both ESD and TEM are commonly used techniques for the treatment of rectal NETs ≤2 cm, but there is no consensus on which of the two treatment options is better.…”
Section: Introductionmentioning
confidence: 99%